2016
DOI: 10.4236/jbise.2016.910b019
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Tortuosity in Hospitalized Patients with Type 2 Diabetes and Diabetic Retinopathy in China

Abstract: Context: Diabetic patients are at high risk for microvascular complications of disease such as diabetic retinopathy (DR) and diabetic neuropathy. Imaging the retinal microvasculature offers a chance to measure quantitatively the microvascular changes in diabetic patients' onset and progression. However, the relation between retinal biomarkers and diabetic risk factors is unclear in Chinese hospitalized type 2 diabetic patients. Aims: To examine the associations of retinal vascular tortuosity with risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The prevalence of diabetes is explosive worldwide, especially in developing countries. 1 In 2019, the Diabetes Atlas of International Diabetes Federation (IDF) (9th Edition) indicated that about 463 million patients exist over the world, which is expected to rise to 700 million in 2045. 2 In China, the number of diabetics has reached 116.4 million, takes up about one third of the amount of diabetics worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes is explosive worldwide, especially in developing countries. 1 In 2019, the Diabetes Atlas of International Diabetes Federation (IDF) (9th Edition) indicated that about 463 million patients exist over the world, which is expected to rise to 700 million in 2045. 2 In China, the number of diabetics has reached 116.4 million, takes up about one third of the amount of diabetics worldwide.…”
Section: Introductionmentioning
confidence: 99%